2013
DOI: 10.1680/macr.12.00198
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on dynamic properties of RC beam

Abstract: The effects of loading rate on the reinforced concrete (RC) beam are experimentally and numerically studied in this paper. First, the effects of strain rate on the reinforcing steel and concrete with different grades are investigated in tests at the strain rates (10 25 /s,0 . 1/s) that might be experienced during earthquakes. Then, the dynamic characteristics of RC beams are given through experiments, and the influences of loading rate on the bearing capacity, ductility, stiffness, failure mode and energy abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…According to the actual needs, different dynamic constitutive models can be selected for the strain rate effect of steel. In this study, the dynamic tensile constitutive model of steel provided in Reference [17] is selected, as shown in the following formulas.…”
Section: Strain Rate Effect Of Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the actual needs, different dynamic constitutive models can be selected for the strain rate effect of steel. In this study, the dynamic tensile constitutive model of steel provided in Reference [17] is selected, as shown in the following formulas.…”
Section: Strain Rate Effect Of Steelmentioning
confidence: 99%
“…Mahin and Bertero [15] along with Li and Li [16] experimentally studied the strain rate effect of reinforcing steel under cyclic loading and found that the yield strength of the reinforcing steel increases with an increasing loading rate. Li and Li [17], Wang et al [18], and Carrillo and Alcoce [19] carried out experimental tests to investigate the dynamic mechanical properties of RC beams, columns, and shear walls. The results showed that the loading rate affects the energy dissipation, stiffness, and strength of RC members to certain extents.…”
Section: Introductionmentioning
confidence: 99%
“…the tangent modulus) is 1% of Young’s modulus. Similar with those of concrete, the elastic modulus and the strain at the maximum stress are less sensitive to the strain-rate variations (Li and Li, 2013). The effect of loading rate on the yield strength and ultimate strength was also presented by the DIF.…”
Section: Fe Simulationmentioning
confidence: 99%
“…Results show that strength reserve of the structure system is experienced when the strain rate effect is accounted for. Li et al investigated the influence of loading rate on the bearing ability, ductility, stiffness, failure mode, and energy absorption of beam specimens by conducting dynamic tests [11]. e dynamic behaviors of columns were studied by Wang et al [12].…”
Section: Introductionmentioning
confidence: 99%